2006
DOI: 10.1007/s11214-006-5670-3
|View full text |Cite
|
Sign up to set email alerts
|

Dynamical Simulations of Plasmapause Deformations

Abstract: Abstract. Dynamical simulations have been developed at IASB-BIRA to model the deformations of the plasmasphere during geomagnetic substorms and other variations in the level of geomagnetic activity. The simulations are based on the mechanism of plasma instability and use the empirical Kp-dependent electric field E5D. The results of the simulations are compared with IMAGE observations that provide the first global comprehensive images of the Earth's plasmasphere. The predicted plasmapause positions correspond g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 9 publications
1
17
0
Order By: Relevance
“…They are formed in the afternoon sector and then rotate eastward with the core of the plasmasphere. Other examples of IMAGE observations during quiet and disturbed periods that have been compared to results of simulations based on the interchange mechanism (IC E5D) have been presented by Pierrard and Cabrera [2005, 2006] and Pierrard [2006].…”
Section: Discussion Of the Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…They are formed in the afternoon sector and then rotate eastward with the core of the plasmasphere. Other examples of IMAGE observations during quiet and disturbed periods that have been compared to results of simulations based on the interchange mechanism (IC E5D) have been presented by Pierrard and Cabrera [2005, 2006] and Pierrard [2006].…”
Section: Discussion Of the Resultsmentioning
confidence: 99%
“…This mechanism has been used in numerical simulations performed by Lemaire [1985, 2000] and by Pierrard and Lemaire [2004]. The positions of the plasmapause predicted by this mechanism with the E5D model have been compared to observations of IMAGE for typical dates [ Pierrard and Cabrera , 2005, 2006; Pierrard , 2006].…”
Section: Dynamical Simulationsmentioning
confidence: 99%
“…Plumes are then formed in the afternoon MLT sector and rotate with the Earth [ Spasojević et al , 2003; Pierrard and Lemaire , 2004; Darrouzet et al , 2006]. The results of the model have been compared to recent observations of Cluster and IMAGE [ Pierrard and Cabrera , 2005, 2006; Pierrard , 2006; Darrouzet et al , 2009] and have shown that the model globally reproduces the dynamic features of the plasmasphere.…”
Section: Introductionmentioning
confidence: 99%
“…They found that the timescale of the plasmapause response to the IMF is about 30 min in their case studies. Furthermore, Pierrard and Cabrera [2005, 2006] presented the simulations of the plasmapause formation and compared the predicted plasmapause positions with the EUV observations. They remarked the correlation between the inward motion of the plasmapause and the southward turning of the IMF in numerical simulations.…”
Section: Introductionmentioning
confidence: 99%